Probing the interactions among sphingosine and phytosphingosine ceramides with non- and alpha-hydroxylated acyl chains in skin lipid model membranes - Čuříková-Kindlová, Barbora Amélie; Diat, Olivier; Štěpánek, František; Vávrová, Kateřina; Zbytovská, Jarmila (International journal of pharmaceutics, 2019)
Ceramides (Cers) are significant constituents of the stratum corneum (SC), the uppermost skin layer responsible for skin barrier properties. Cers are a heterogeneous group of lipids whose mutual interactions are still unclear. To better understand these interactions, we characterized model membranes containing stearic acid, cholesterol, cholesterol sulfate and one or more of the following ceramides: N-stearoyl-sphingosine (CerNS), N-stearoyl-phytosphingosine (CerNP) and N-(2-hydroxy)stearoyl-phytosphingosine (CerAP). Small angle X-ray scattering and FTIR spectroscopy were used to study lipid arrangement, phase separation and thermotropic behaviour. In the one-Cer systems, the membranes with CerNP showed strong hydrogen bonding and significant phase separation, even after phase transition, while the systems containing CerAP and CerNS had increased lipid miscibility. The multi-Cer systems exhibited different behaviour. In particular, the membrane containing all three Cers was a highly miscible system with narrow one-step phase transition, which, of all the studied samples, occurred at the lowest temperatures. Our results show that even a small variation in Cer structure results in substantially different phase behaviour, which is further affected by the presence of other Cer subclasses. Interestingly, the phase behaviour of the most complex three-Cer system was simpler than that of the others, highlighting the importance of lipid diversity in real SC.
Keywords: Temperature; Hydroxylation; sfingosin; hydroxylace; Stratum corneum lipids; Phase Transition; FTIR; Ceramides; kůže; Membrane Lipids; Model membranes; Skin delivery; Skin; ceramidy; X-ray scattering; teplota; membránové lipidy; změna skupenství; Sphingosine